How to create commercial value from patents: the role of patent management. (20th May 2016) - Ernst, Holger; Conley, James; Omland, Nils
Abstract : This article examines the relationship between patent management and indicators of a firm's financial and patenting performance. The empirical analyses are based on a sample of 158 technology‐based firms from the United States and Germany across multiple industries. The results show that two important dimensions of patent management, specifically patent protection management and patent information management, are positively correlated with a firm's level of financial profitability and the strategic and financial impact of its patent portfolio. This implies that patent protection and information management are important managerial capabilities of the firm that determine the level of value it can create from patents. We further find that a firm's technology strategy moderates the relationship between patent protection management and firm performance; it does, however, not moderate the relationship between patent information management and firm performance. Hence, the effectiveness of certain managerial capabilities on value creation from patents are contingent upon specific boundary conditions. Our findings have implications for improving firm performance through patent management.